Ulama Minangkabau dan Sastra: Mengkaji Kepengarangan Syekh Abdullatif Syakur Balai Gurah - Apria Putra (Diwan: Jurnal Bahasa dan Sastra Arab, 2017)
This article encompasses a study of the Sheikh Abdullatif Syakur’s authorship, particularly literary valuable essays. This study departs from the productivity of Sheikh Abdullatif in composing Arabic and Minangkabau with uslub literature. Syekh Abdullatif Syakur's works are interesting to study for several considerations, (1) high intensity in teaching Arabic and recitations of the Qur'an with various methods, (2) his proximity to the tradition of society shown by his essay in the form of nazham, (3) his tenacity in teaching and preaching, and (4) his passion for reading literary texts. Based on that, this study discusses two of Syekh Abdullatif Syakur literary works, namely the book of Khitabah and Nazham Nasehat. The authorship of Sheikh Abdullatif was influenced by several aspects, including his interest in Arabic, his desire to provide knowledge to the community, social conditions in his hometown, the productivity of his teacher in Mecca, and reading books that became his amusement.